Analisis Hukum terhadap Pelaksanaan Musyawarah Perencanaan Pembangunan (Musrenbang) di Kecamatan Krejengan Kabupaten Probolinggo Berdasarkan Permendagri Nomor 86 Tahun 2017 - Khusnul khitaminah; Qurrata a'yun; Muhammad Hendra; Abdur Rohim (Jurnal Hukum Lex Generalis, 2026)
Development Planning Deliberation (Musrenbang) is a participatory mechanism regulated under Minister of Home Affairs Regulation No. 86 of 2017 to ensure public involvement in regional development planning. This study analyzes its implementation inKrejengan District,ProbolinggoRegency, from legal perspective. This empirical legal research uses the statutory and the sociological approaches. The findings show that Musrenbang has normatively followed the required stages, but faces challenges such as low participation, limited human resources and weak policy synchronization. Strengthening supervision, transparency and accountability is necessary to ensure its effectiveness as a participatory planning instrument.